2016
DOI: 10.17507/tpls.0604.22
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Relationship between Self-regulation and Reading Comprehension

Abstract: Abstract-Over the past three decades, researchers have found that motivational variables have an effective role in language skills and in academic achievement and success (Khajavi & Abbasian, 2013). An attempt was made in the present research to review the relationship between self-regulation as one of the motivational variables and reading comprehension. Moreover, the present paper is organized in the way that some of the significant notions of self-regulation and cyclical phases, and some models of self-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The results of this study conducted in PFL context are in line with those of some earlier studies conducted in EFL contexts. For example, the results of the study carried out by Nejadihassan and Arabmofrad (2016) demonstrated that Iranian EFL learners can increase S‐R which can lead to improving their reading comprehension. Moreover, the results of Parker's (2016) study showed that S‐R had a significant relationship with reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study conducted in PFL context are in line with those of some earlier studies conducted in EFL contexts. For example, the results of the study carried out by Nejadihassan and Arabmofrad (2016) demonstrated that Iranian EFL learners can increase S‐R which can lead to improving their reading comprehension. Moreover, the results of Parker's (2016) study showed that S‐R had a significant relationship with reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that S‐R presented a significant link to reading comprehension. In Iranian EFL context, Nejadihassan and Arabmofrad (2016) probed whether high self‐regulated learners have a high level of reading comprehension. The findings illustrated that learners can improve S‐R by utilizing some strategies, and also through these can develop their reading comprehension ability; that is, S‐R is a determinative factor of learners' learning processes.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that metacognitive monitoring and self-regulated learning strategies are beneficial in enhancing procedural learning [44]. By monitoring and regulating their processing of novel information, students can evaluate their ongoing comprehension and employ repair strategies, if needed [45].…”
Section: Educational Implicationmentioning
confidence: 99%
“…In online learning, the students are expected to use motivation to comprehend the provided learning texts so that they can achieve learning goals. Motivation can significantly influence the students to push themselves by comprehending the provided text so that they can achieve full understanding and complete their tasks (Nejadihassan & Arabmofrad, 2016;Takaloo & Ahmadi, 2017). Nevertheless, although a number of previous studies have investigated the challenges of online learning and the urgency for self-regulation, studies that investigate students' self-regulation in reading comprehension during an online class are still underrepresented.…”
Section: Introductionmentioning
confidence: 99%